The additional value of self-reflection and feedback on therapy outcome: a pilot study - Kamp, David; Blanker, Cynthia; Hafkenscheid, Anton; van Os, Jim (Frontiers in Psychology, 2024)
IntroductionOver the past few decades, psychotherapy research was dominated by testing the efficacy of “brand name” therapeutic techniques and models. Another line of research however, suggests that common factors, such as the therapeutic alliance and empathy, might play a greater role in effective therapy than specific therapeutic techniques and models. Routine process monitoring (RPM), focusing on common factors, has emerged as a promising approach to enhance therapy outcomes. This ongoing feedback loop aims to improve the therapeutic alliance and to address countertransference issues, potentially leading to better therapy outcomes.MethodsA total of 131 patients above the age of 18 were included into the sample. The design of the study consisted of three stages, in which two kinds of instruments to measure the therapeutic alliance and countertransference were administered, namely the Session Rating Scale (SRS) and a brief version of Impact Message Inventory-Circumplex (IMI-CS). The Outcome Rating Scale (ORS) was used as an outcome measure. Depending on the stage of the study, these three instruments were administered every time a patient had a psychotherapy session.ResultsPatients reported improved outcomes on the ORS in T2 compared to T1 (p = 0.011). Furthermore, a significant increase in the strength of the therapeutic relationship, as measured by the SRS, occurred between T2 and T3 (p = 0.031). A positive correlation was found between SRS scores and the “friendly” position on the IMI-CS (p = <0.000), while a negative correlation was found between SRS ratings and the “submissive” position on the IMI-CS (p = 0.019).DiscussionPatients experienced improvements and might attribute part of their improvement to the relationship with their therapists, evaluating the therapeutic alliance more positively in the later stages of their treatment. Despite methodological challenges, such as varying treatment durations and pre-existing therapist-patient relationships, the findings highlight the value of patient engagement and therapist self-reflection. This study supports the utility of deliberate practice in psychotherapy, suggesting it can enhance therapeutic outcome and laying the groundwork for future research.